Essential oil of Lippia alba in the transport of Nile tilapia - Hohlenwerger,Janis Cumming (2017)
ABSTRACT: This study aimed to examine the action of the essential oil of Lippia alba (EOLA) in the stress response for transport of Nile tilapia Oreochromis niloticus . The fish were transported into three treatments (in triplicate): control, 10 and 20 µL L-1 EOLA, with loading density of 15 fish/plastic bags for 8h. Plasma glucose levels were significantly decreased in fish exposed to 20µL L-1 EOLA in comparison with the control group and fish exposed to 10µL L-1 EOLA, but the plasma cortisol, lactate and paraoxonase levels were similar. Un-ionized ammonia and ventilatory rate demonstrated a significant reduction in the treatments with the use of EOLA. In conclusion the use of 20µL L-1 EOLA is indicated for Nile tilapia transport.